Adaptation to climate change among transhumant herders: evidences from northern Benin (West Africa) - Djakpa, Milka Grâce; Egah, Janvier; Degla, Pamphile (Frontiers in Sustainable Food Systems, 2024)
Climate change and related effects such as water scarcity is a major issue for transhumant who need to develop sustainable adaptation strategies. We highlighted both the perceived climate change effects and the main socio-economic drivers of the decisions to use specific adaptation strategies. Our study used primary data collected through a survey approach from 100 transhumant randomly selected in two municipal areas in the northern of Benin. We used descriptive statistics and a multivariate regression model to analyze our data.Transhumant herders perceived climate change effects through variability of rainfall, of temperature and of wind direction. In response to the perceived changes, they adopted several strategies, including cattle complementary feed search, water for drinking and improving genetic performance for their cattle. The perceived changes and sociodemographic characteristics including religion, sociocultural group, etc. negatively influenced the adoption of some adaptation strategies such as forage reserves and changing transhumance area and routes. In the other hand, the perceived changes and socioeconomic characteristics including age, education, religion, etc. positively influenced the adoption of food stockpiling, of prayers and offering to deities, of changing the transhumance period, etc. The perception of the climate change effects and the sociodemographic characteristics of the transhumant herders affected the adoption of adaptation strategies in many ways. Policy makers could deliver climate information for strengthening the resilience of transhumant herders.